Pre- And Post-Pandemic Financial Performance: Comparative Analysis Of Profitability, Liquidity, And Solvency Ratios In The Idx Lq45 Banking Sector (2019-2023) - Kurniawan, M. Yusuf; Arumsari, Yuni Kusuma; Napitupulu, Tesalonikayani (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This study analyzes the financial performance of five banking companies in the IDX LQ45 index during 2019–2023, focusing on profitability, liquidity, and solvency before and after the COVID-19 pandemic. A descriptive quantitative approach is employed using secondary data from annual financial statements. The analysis utilizes financial ratios, including Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) for profitability; Current Ratio (CR) and Quick Ratio (QR) for liquidity; and Debt to Equity Ratio (DER) and Debt to Assets Ratio (DAR) for solvency. The data is analyzed using the Paired Sample T-Test in SPSS version 29. The findings indicate a significant decline in profitability during the pandemic, followed by a recovery trend in 2023. Liquidity and solvency remained stable due to government interventions and effective risk management. These results provide insights for regulators and investors regarding the banking sector’s resilience against economic shocks and the effectiveness of risk mitigation strategies.